Using Macromedia Flash Application to Improve Students’ Vocabulary Mastery - Sitra Hamsi Padaloi Hamsi; Nanning (Inspiring: English Education Journal, 2021)
This research aims to determine whether the use of the Macromedia flash application in the learning process can improve vocabulary mastery at the seventh grade of SMPN 4 Mattiro sompe Kab. Pinrang. Using media in teaching has the main aim, namely to make it easier for students to understand the material given, improve students’ understanding and mastery of vocabulary effectively and efficiently and can increase student interest in learning English. In this research, the researcher used pre-experimental design comprising pre-test and post-test, which is the different between pre-test and post-test scores is influenced by the treatment given to student. The success of the treatment is determined by comparing pre-test and post-test score. In the collecting data, the researcher used an instrument test that comprises pre-test and post-test. The result showed that Macromedia flash application can improve students’ vocabulary mastery. It showed by the students’ mean score of post-test (81.91) was greater than pre-test (59.82). Even, for the level significant (p) 0.05 and df: 22, and the value of t-table is 1.717 while the value of t-test is 14.43. It means that the value of t-test is greater than the value of t-table (14.43 ≥ 1.717). Thus, it can be concluded that the students’ vocabulary is significantly better after getting treatment by using Macromedia flash application. So, the null hypothesis (H0) was refused and the alternative hypothesis (H1) was accepted. The results of the questionnaire show that there are several problems faced by students in increasing their vocabulary, including students having difficulty understanding vocabulary without objects, memorizing vocabulary, making students difficult to understand vocabulary and students having difficulty understanding the pronunciation of words when learning English.